Does Access to Aid and Budget Improve the Welfare of Farmer Households in Palopo, Indonesia - Harahap, Burhanuddin; Widodo, Wahyu; Sutanto, Adi; Sapar, Sapar; Syafruddin, Syafruddin (AMCA Journal of Community Development, 2024)
Purpose.The agricultural industry significantly contributes to poverty alleviation, particularly in rural regions as opposed to metropolitan ones. Hence, government programs should be able to target the areas afflicted by poverty effectively. Rural regions serve as the hub of commercial operations and play a crucial role in safeguarding and empowering farmers, particularly those who are small-scale. Methodology / approach. This research aims to analyze the access to assistance and agricultural estimates by examining farmers' prescriptions using the Structural Equation Modeling (SEM) approach. Results. The objective is to determine if there is an impact on the growth in farm family welfare in the City of Palopo based on data from 105 farmers. This study utilises a descriptive and explanatory methodology, including quantitative techniques and inferential statistical analysis via Structural Equation Modelling (SEM) utilising Partial Least Squares (PLS). The results indicated that (X1) assistance had a very significant positive impact of 98.26% on the well-being of (Y) farmers' families. However, (X2) did not have a significant beneficial influence on (Y). Originality / scientific novelty. It was found that the access of farmer group households to agricultural assistance and the sustainable use of budgets and their very effective distribution in general can be said to greatly improve the welfare of farmer group households. This research is topically broader in scope making it very specific based on the scope of sources in Palopo, Indonesia. As far as is known, these results have not been previously reported. Practical value / implications. Management in the distribution of aid and access to agricultural budgets which are very vulnerable to misappropriation by the state apparatus has been identified as not improving the welfare of farmer households. One very effective way is to increase inherent surveillance.